Head impact characteristics based on player position in collegiate soccer athletes - Nelson, K. M.; Daidone, E. H. K.; Breedlove, K. M.; Bradney, D. A.; Bowman, T. G. (International Journal of Athletic Therapy & Training, 2021)
The study objective was to determine the magnitude and frequency of head impacts in NCAA Division III soccer athletes based on player position and type of play (offense, defense, transition). Across player position, male and female soccer defenders sustained the most head impacts (males IR = 18.89, 95% CI = 16.89-20.89; females IR = 8.45, 95% CI = 7.25-9.64; IRR = 2.23, 95% CI = 1.87-2.67). The study revealed a nonstatistically significant interaction between sex, player position, and type of play for both linear (p = .42) and rotational accelerations (p = .16). Defenders sustained the majority of the head impacts in the study sample, suggesting preventative initiatives should be focused on back row players.